Prostate-specific membrane antigen ligands for imaging and therapy - Eiber, Matthias; Kratochwil, Clemens; Giesel, Frederik L. (Journal of nuclear medicine, 2017)
The prostate-specific membrane antigen (PSMA) is highly expressed on most prostate cancer (PC) cells. Therefore, the targeting of PSMA has become increasingly important over the last decade. Glu-urea-based PSMA ligands used for both imaging and radioligand therapy are the mainstays of the current success. For PET imaging, both 68Ga- and 18F-labeled agents have been successfully translated to clinical applications. Mainly retrospective cohort studies have shown a high value in the setting of biochemical recurrence, with high detection rates even in the presence of low prostate-specific antigen levels. Preliminary data indicated that radioguided surgery with PSMA ligands may help to further improve patient outcomes because it facilitates the removal of small tumor deposits that are otherwise difficult to detect. For primary PC, PSMA ligand PET imaging has been shown to be superior to cross-sectional imaging for the detection of metastatic lymph nodes. In addition, it promises to also provide intraprostatic tumor localization, especially when used in combination with multiparametric MRI. Increasing numbers of studies have reported considerable changes in management resulting from PSMA ligand PET imaging for both biochemical recurrence and primary disease. The use of 177Lu-PSMA-based radioligand therapy has demonstrated a reasonable response, mainly as defined by a prostate-specific antigen response of more than 50%, comparable to other recently introduced agents. Especially given the high level of safety of 177Lu-PSMA radioligand therapy, with only minimal grade 3 and 4 toxicities reported so far, it has the potential to expand options for metastatic castration-resistant PC. This review is intended to provide a comprehensive overview of the current literature on low-molecular-weight PSMA ligands for both PET imaging and therapeutic approaches, with a focus on agents that have been clinically adopted.